EMPOWERING SMALL AND MEDIUM ENTERPRISES THROUGH AUGMENTED REALITY TECHNOLOGY FOR BRANDING AND PROMOTING TRADITIONAL PALEMBANG CAKES - Putri, Aulia Utami; Imania, Katriza; Rahmawati, Annisa; Sevtiani, Alvina; Saputri, Efrilia Wanda; Fathiyah, Nabila Trisya (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Palembang city is known as a culinary destination with a variety of traditional cakes such as Kue Gandus, Ketan Kuning Serundeng, Kojo, Muso, and Srikaya, which are local cultural identities. Micro, Small, and Medium Enterprises (MSMEs) like Dapoer Endungqu play an important role in preserving this culinary tradition, but face challenges in digital marketing and branding. This service activity aims to empower MSMEs through Augmented Reality (AR) technology to enhance the promotion and branding of traditional Palembang cake products. The implementation method uses a participatory approach that includes initial observation and identification of partner needs, product sampling, AR-based digital media design, and partner training and mentoring. The results show an increase in partner capacity in product photography, the use of interactive AR catalogues, and social media management, which strengthens visual appeal, consumer interaction, and promotional reach. The discussion confirms that AR effectively increases customer trust and loyalty without diminishing cultural value. The conclusion confirms that AR integration can strengthen the competitiveness of MSMEs in the digital age. Follow-up includes further development of the AR application, periodic monitoring, and program expansion to other culinary MSMEs for innovation and sustainability.